Dopamine and serotonin genetic risk scores predicting substance and nicotine use in attention deficit/hyperactivity disorder. (6th March 2015) - Groenman, Annabeth P.; Greven, Corina U.; van Donkelaar, Marjolein M. J.; Schellekens, Arnt; van Hulzen, Kimm J. E.; Rommelse, Nanda; Hartman, Catharina A.; Hoekstra, Pieter J.; Luman, Marjolein; Franke, Barbara; Faraone, Stephen V.; Oosterlaan, Jaap; et al.
Abstract: Individuals with attention deficit/hyperactivity disorder (ADHD) are at increased risk of developing substance use disorders (SUDs) and nicotine dependence. The co‐occurrence of ADHD and SUDs/nicotine dependence may in part be mediated by shared genetic liability. Several neurobiological pathways have been implicated in both ADHD and SUDs, including dopamine and serotonin pathways. We hypothesized that variations in dopamine and serotonin neurotransmission genes were involved in the genetic liability to develop SUDs/nicotine dependence in ADHD. The current study included participants with ADHD ( n  = 280) who were originally part of the Dutch International Multicenter ADHD Genetics study. Participants were aged 5–15 years and attending outpatient clinics at enrollment in the study. Diagnoses of ADHD, SUDs, nicotine dependence, age of first nicotine and substance use, and alcohol use severity were based on semi‐structured interviews and questionnaires. Genetic risk scores were created for both serotonergic and dopaminergic risk genes previously shown to be associated with ADHD and SUDs and/or nicotine dependence. The serotonin genetic risk score significantly predicted alcohol use severity. No significant serotonin × dopamine risk score or effect of stimulant medication was found. The current study adds to the literature by providing insight into genetic underpinnings of the co‐morbidity of ADHD and SUDs. While the focus of the literature so far has been mostly on dopamine, our study suggests that serotonin may also play a role in the relationship between these disorders. Abstract : Several neurobiological pathways have been implicated in both ADHD and SUDs, including dopamine and serotonin pathways. We hypothesized that variations in dopamine and serotonin neurotransmission genes were involved in the genetic liability to develop SUDs/nicotine dependence in ADHD. The serotonin genetic risk score significantly predicted alcohol use severity in ADHD. While the focus of the literature so far has been mostly on dopamine, our study suggests that serotonin may also play a role in the relationship between these disorders.